UPAYA GURU MELATIH KONSENTRASI SISWA DALAM PEMBELAJARAN DI KELAS II SDN 177 PEKANBARU - Ranisha Dian Insani; Dea Mustika (STKIP Subang, 2023)
Student concentration in learning is very important for the success of the teaching and learning process. In order to train students' concentration in learning, a teacher must make efforts to train students' concentration. This study aims to determine the teacher's efforts and the impact of the teacher's efforts to train students' concentration in learning in class II SDN 177 Pekanbaru. This research uses descriptive qualitative method. Data collection instrument techniques in this study used interviews, observation and documentation. Testing the validity of the data using triangulation. Data analysis techniques namely data collection, data reduction, data presentation and drawing conclusions. The results showed that the teacher had tried to train students' concentration in learning. The conclusion from the research results is that the efforts made by the teacher are completing learning tools, designing learning media, checking student readiness, instilling interest in learning in students, using various learning methods, and creating a conducive learning environment. While the impacts include students who are more enthusiastic, more active and more focused and conditioned during the learning process.